2004
DOI: 10.1002/art.20675
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the oxygen concentration gradient from the synovial surface of articular cartilage to the cartilage–bone interface: A modeling study

Abstract: Objective. There is very little information on the gradients of oxygen concentration from the synovial surface to the subchondral bone in articular cartilage. Cartilage is usually regarded as hypoxic, even though cellular metabolism is inhibited at low oxygen concentrations. We therefore measured rates of cellular consumption of oxygen and used these rates to calculate oxygen tension profiles across articular cartilage.Methods. The rate of oxygen consumption by bovine articular chondrocytes was measured in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
222
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 240 publications
(228 citation statements)
references
References 44 publications
3
222
0
2
Order By: Relevance
“…But this was not the case, as the THP-1 cells showed a normal respiration pattern. Zhou et al (2004) found an oxygen uptake rate for chondrocytes of maximum 10.81 nmol/10 6 cells/h, corresponding to 180.16 pmol/min/ 10 6 , thus corresponding to aerobic cells like the thymic cells which consumed about 200 pmol 02/min/10 6 cells (Verlaet et al, 2002).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…But this was not the case, as the THP-1 cells showed a normal respiration pattern. Zhou et al (2004) found an oxygen uptake rate for chondrocytes of maximum 10.81 nmol/10 6 cells/h, corresponding to 180.16 pmol/min/ 10 6 , thus corresponding to aerobic cells like the thymic cells which consumed about 200 pmol 02/min/10 6 cells (Verlaet et al, 2002).…”
Section: Discussionmentioning
confidence: 93%
“…But Zhou et al (2004) worked on bovine articular cartilage from 18 to 24 months old steers without preliminary culture period at 5% O 2 tension and exposed the chondrocytes to 3 g/L glucose in the medium during oxymetry. Some authors used chondrocytes cell lines (Moulton et al, 1997), chondrocytes isolated from the ribs, the nasal septum (covered throughout the lifetime by the perichondrium), the growth plate or the intervertebral disc [known to have a PO 2 of only 2-8 mmHg in its deepest layers (Grimshaw and Mason, 2000)].…”
Section: Discussionmentioning
confidence: 99%
“…O 2 measurements. Oxygen consumption rates (nmoles/ million cells/hour) were measured on cell suspensions using a Clark electrode in a sealed water-jacketed chamber (Strathkelvin Instruments, Glasgow, UK) (21). The pH did not fall during the 30-minute measurement period.…”
Section: Methodsmentioning
confidence: 99%
“…Oxygen consumption was modelled separately for each cell phenotype using Michealas-Menten kinetics [39][40][41] . In the equation shown, each phenotype was represented by n, whereby n = 1 represents MSCs; n = 2 represents CCs; n = 3 represents OBs; n = 4 represents FBs; n = 5 represents AB and; n = 6…”
Section: Oxygen Transportmentioning
confidence: 99%
“…In addition to this a constant oxygen boundary condition of 5 % was applied to the surface of the defect in order to simulate the nutrient supply from the synovial fluid 41,42 . Finally, based on the in silico study conducted by Zhou et al 41 , the following three assumptions were made: 1) The synovial fluid was well mixed and as such any gradients within the fluid were negligible 2) Oxygen transport was steady-state, meaning that the effects of mechanical loading and cartilage deformation on oxygen transport were ignored 3)…”
Section: Oxygen Transportmentioning
confidence: 99%